Exiting the State and Debunking the State of Nature - Hanna, Robert (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Contrary to the belief of most Kantians and Kant scholars, Kant is in fact an anarchist. In this paper, I distinguish sharply between two concepts of enlightenment, enlightenment lite and heavy duty or radical enlightement ; show how there is an unbridgeable gap between Kant’s official political theory in The Doctrine of Right and his ethics; show how Kant’s real political theory is worked out in Religion Within the Boundaries of Mere Reason, and is in fact a heavy-duty, radically enlightened version of anarchism; refute and debunk widely-believed Hobbesian assumptions about human nature, which are in fact nothing but cognitive illusions; and propose a de-biasing strategy in political aesthetics for ridding ourselves of these Hobbesian cognitive illusions.